Spinoza and the Possibility of Adequate Ideas - Thaddeus Robinson (Journal of Modern Philosophy)
Adequate ideas are the fundamental element of Spinoza’s epistemological program. However, a recurrent worry among scholars is that Spinoza’s account of adequate ideas is inconsistent with any finite being ever having one. As I frame it, the problem is that for Spinoza an idea is adequate in a mind only if all its causal antecedents lie within the mind as well. However, it seems there can be no finite mind for which this is true; finite minds come to be and exist within a deterministic causal nexus, and the causal antecedents of every idea in a mind will ultimately stretch far beyond it. I call this the External Cause Objection. I argue that Spinoza appreciated and explicitly answered this concern. According to this reply, adequate ideas do not have causes external to the mind because they do not fall into the category of what Spinoza calls “singular things.” In addition to showing that this coheres with his more specific claims about adequate ideas and his firm belief that finite minds are parts of nature, I argue that the resolution to this problem sheds light on Spinoza’s understanding of what I call absolute agency.